RepeatsDB in 2021: improved data and extended classification for protein tandem repeat structures. Issue Volume 49:Issue D1(2021) (25th November 2020) - Paladin, Lisanna; Bevilacqua, Martina; Errigo, Sara; Piovesan, Damiano; Mičetić, Ivan; Necci, Marco; Monzon, Alexander Miguel; Fabre, Maria Laura; Lopez, Jose Luis; Nilsson, Juliet F; Rios, Javier; Menna, Pablo Lorenzano; et al.
Abstract: The RepeatsDB database (URL: https://repeatsdb.org/ ) provides annotations and classification for protein tandem repeat structures from the Protein Data Bank (PDB). Protein tandem repeats are ubiquitous in all branches of the tree of life. The accumulation of solved repeat structures provides new possibilities for classification and detection, but also increasing the need for annotation. Here we present RepeatsDB 3.0, which addresses these challenges and presents an extended classification scheme. The major conceptual change compared to the previous version is the hierarchical classification combining top levels based solely on structural similarity (Class > Topology > Fold) with two new levels (Clan > Family) requiring sequence similarity and describing repeat motifs in collaboration with Pfam. Data growth has been addressed with improved mechanisms for browsing the classification hierarchy. A new UniProt-centric view unifies the increasingly frequent annotation of structures from identical or similar sequences. This update of RepeatsDB aligns with our commitment to develop a resource that extracts, organizes and distributes specialized information on tandem repeat protein structures.